A reflective metasurface for broadband OAM vortex wave generation - Zhang, Meng; Li, Desen; Lin, Jiahan; Zhang, Bingzhi; Tao, Jifang; Zhao, Zhenxue; Zeng, Yuan; Shang, Wenli; Zhang, Wu (Frontiers in Physics, 2022)
In this paper, we proposed a reflective metasurface which controls the phase delay of the electromagnetic (EM) wave through geometric phase manipulation. By coding the metasurface unit cells in different orientation angles, an orbital angular momentum (OAM) wave can be obtained through the metasurface reflection. A broadband reflective OAM wave with mode l = -1 was demonstrated which was experimentally observed from 8.3 GHz to 11.6 GHz. The mode spectrum of OAM wave was analyzed and the spectrum weight was about 0.82 through numerical calculation and about 0.47 through experimental measurement for the mode l = -1. The realization of this broadband OAM wave has the potential application to improve the OAM wave based communication capacity.